STUDI PENERAPAN REGULASI DALAM PENYEDIAAN FASILITAS UMUM DAN FASILITAS SOSIAL PADA KLUSTER APARTEMEN DI JAKARTA: STUDI KASUS: APARTEMEN SKY TERRACE DAN APARTEMEN GREEN BAY - Agustin, Laura Tri; Tresani, Nurahma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Indonesia is going through a rapid development and an excessive urbanization. The demand in residential sector had been growing each year, until the year 1990 when both Indonesian government and private developers started to focus on developing residential sector, from clustered houses to apartment complex. Public and social facilities is one of the mandatory requirements for both landed and apartment residentials provided by the developers. However, the provision of public and social facilities have proven to meet many obstacles along the way. The purpose of this research is to identify the process of public and social facilities regulation use, and to identify the root of the problem of public and social facilities application in clustered apartment projects in Jakarta, by reviewing chronologically the government regulation and the disposition process, the application by developers, observation system by the government during operational, and the handover from developers to the government. In the process of reviewing the matter thoroughly, this research is done by focusing on the main proposition, which is on “How to apply the public and social facilities regulation in clustered apartment?”. To support the conclusion of the main proposition, the supporting conclusion are: (1) How was the government regulation forming process on public and social facilities in clustered apartment? (2) How is the application done by developers on public and social facilities in clustered apartment? (3) How is the observation done by the government’s authority during application and handover of public and social facilities in clustered apartment. To provide answers for the proposition conclusion above, this research is done by explorative study research method and instrumental case study approach, where the researcher will focus on the understanding of an issue or theory which will be supported by case study. The instruments that was used in this research is thorough interview, documentation and observation. As for the location limitation was determined by the numbers of inhabitants. The case study for this research are Sky Terrace apartment in West Jakarta with 2.014 inhabitants, and Green Bay apartment in North Jakarta with 34.048 inhabitants. Keywords: Apartment, vertical, regulation, residensial, cluster, facilities, public